Empirical Analysis of X-efficiency and Profitability of Commercial Banks in Canada - Liu, Yitong (2017)
This paper will examine the efficiency and profitability of Canadian banking sector. The idea is to take a two-stage approach to test determinants of profitability over the period of 2010-2016 with respect to bank’s efficiency performance. In the first stage, the model will be focused on estimations using Stochastic Frontier Analysis (SFA) of cost functions to get the efficiency score for Canadian banks. Then in the second stage, estimations using Generalized Method of Moments (GMM) will be modeled to find out the significant variables influencing bank’s profitability, along with consideration of the efficiency score from the first stage and calculated Z score along with internal and external variables. Results indicate that efficiency has positive and significant impact on bank’s profitability, while Z score and other factors demonstrate mixed effects.